The Sirt1/P53 Axis in Diabetic Intervertebral Disc Degeneration Pathogenesis and Therapeutics. (9th September 2019) - Zhang, Zengjie; Lin, Jialiang; Nisar, Majid; Chen, Tingting; Xu, Tianzhen; Zheng, Gang; Wang, Chenggui; Jin, Haiming; Chen, Jiaoxiang; Gao, Weiyang; Tian, Naifeng; Wang, Xiangyang; et al.
Abstract : Intervertebral disc degeneration (IDD) is one of the major causes of low back pain. Diabetes is a risk factor for IDD and may aggravate IDD in rats; however, the mechanism is poorly understood. Previously, we demonstrated that apoptosis and senescence were increased in diabetic nucleus pulposus (NP) tissues; in the current study, we found that hyperglycaemia may promote the incidence of apoptosis and senescence in NP cells in vitro . Meanwhile, the acetylation of P53, a master transcription factor of apoptosis and senescence, was also found increased in diabetic NP tissues in vivo as well as in hyperglycaemic NP cells in vitro . Sirt1 is an NAD + -dependent deacetylase, and we showed that the expression of Sirt1 was decreased in NP tissues, while hyperglycaemia could suppress the expression and activity of Sirt1 in NP cells. Furthermore, we demonstrated that butein may inhibit acetylation of P53 and protect NP cells against hyperglycaemia-induced apoptosis and senescence through Sirt1 activation, as the Sirt1 inhibitor Ex527 may counteract the protective effect of butein in hyperglycaemic NP cells. An in vivo study showed that butein could ameliorate the IDD process in diabetic rats, while Sirt1 was increased and acetyl-p53 was decreased in NP tissues in butein-treated rats. These results indicate that the Sirt1/P53 axis is involved in the pathogenesis of diabetic IDD and may serve as a therapeutic target for diabetic IDD.